Dosage compensation in Drosophila: The X-chromosomal binding of MSL-1 and MLE is dependent on Sxl activity. - Hilfiker, A.; Yang, Y.; Hayes, D.H.; Beard, C.A.; Manning, J.E.; Lucchesi, J.C. (The EMBO Journal, 1994)
In Drosophila, dosage compensation, i.e. the equalization of levels of X-linked gene products in the two sexes, is achieved by the hypertranscription of most X-linked genes in males relative to females. The products of at least four genes, collectively termed male-specific lethal (msl) genes, are required for this process and, at least in the case of three of them, mediate this function through an association with the X chromosome in males. We have studied some of the parameters that affect the association of the msl-1 gene product and found that its presence is dependent on the wild-type function of the other three genes, leading to the conclusion that these gene products contribute to the formation of a multi-subunit complex. Furthermore, the X-chromosomal association of the msl-1 and mle gene products is negatively correlated with the level of function of the master regulatory gene Sxl and can assume either a mosaic or a uniform distribution in the tissues of mutant XX individuals. Surprisingly, we also found that the association of these two msl gene products with the two X chromosomes in females of certain mutant genotypes does not result in the hypertranscription of X-linked genes or in any apparent reduction in viability.